(untitled) (MMIT Proceedings, 2025)
This article is based on the study of digital technology and the development of international financial relations in Uzbekistan. The main purpose of the research is to analyze the role and potential of digital technologies in shaping international financial relations in the Republic of Uzbekistan, as well as to identify ways to enhance the effectiveness of financial integration and cross-border operations through the use of modern digital solutions.